Autoimmune Hepatic Failure Following Acute Hepatitis A is Accompanied by Inflammatory Conversion of Regulatory T Cells - Leem, Galam; Kim, Beom Kyung; Shin, Eui-Cheol; Park, Jun Yong (Yonsei medical journal, 2020)
To evaluate the pathophysiology of autoimmune hepatitis (AIH) following acute hepatitis A (AHA) in immunologic aspects, we performed multi-color flow cytometry with peripheral blood mononuclear cells of a patient who underwent liver transplantation due to AIH-induced liver failure. Unlike general AHA patients, the proportion of tumor necrosis factor-α-producing Treg cells remained high for 6 months after diagnosis of AHA until she underwent a liver transplantation. The conversion of Treg cells into mediators of inflammation may have played a role in the autoimmune pathogenesis following AHA.